2014
DOI: 10.4168/aair.2014.6.6.517
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Indoor Air Pollutant Levels and Residential Environment in Children With Atopic Dermatitis

Abstract: PurposeThis study was aimed to investigate the relationship between indoor air pollutant levels and residential environment in children with atopic dermatitis (AD) living in Seoul.MethodsA total of 150 children with AD were included. Residential environment was assessed by questionnaires which were completed by their parents. To evaluate the level of exposure to the indoor air pollutants, concentrations of the indoor air pollutants including particulate matter with diameter less than 10 µm (PM10), formaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 35 publications
(38 reference statements)
1
37
1
1
Order By: Relevance
“…These high concentrations were similar to the results shown in a previous study that measured the indoor air quality in an unoccupied newly built building [22]. The reason that high levels of TVOCs were measured in our study is due to the use of artificial air fresheners or air cleansing, air ventilation, location, and floor level of the apartment, and the surrounding region/area [21,22]. High concentrations of VOCs or formaldehyde are associated with the onset of Sick Building Syndrome (SBS) or the aggravation of allergic diseases in newly built buildings [4,23,24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These high concentrations were similar to the results shown in a previous study that measured the indoor air quality in an unoccupied newly built building [22]. The reason that high levels of TVOCs were measured in our study is due to the use of artificial air fresheners or air cleansing, air ventilation, location, and floor level of the apartment, and the surrounding region/area [21,22]. High concentrations of VOCs or formaldehyde are associated with the onset of Sick Building Syndrome (SBS) or the aggravation of allergic diseases in newly built buildings [4,23,24].…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reported that the concentration of VOCs in the indoor air of houses of patients with AD and allergic asthma was approximately 1.4–2.0 fold higher than in the houses of the same age group without atopy [7]. In our study, the concentrations of TVOCs were found to be higher than values in previous studies on eco-friendly materials or in the houses of patients with AD [19,20,21]. These high concentrations were similar to the results shown in a previous study that measured the indoor air quality in an unoccupied newly built building [22].…”
Section: Discussioncontrasting
confidence: 70%
“…Although the occurrence of AD is associated with genetic factors, [10,11] recent increase in incidence rate is more likely attributed to environmental factors, [1214] such as pollution and aeroallergens (e.g., pet hair, house dust mite, and pollen). [15] In addition, changing lifestyles, such as frequent bathing, regular use of soap, and living in concrete jungles with air conditioning that dehumidifies the air, may accelerate stratum corneum (SC) barrier impairment. [16] …”
Section: Discussionmentioning
confidence: 99%
“…Indoor air pollution concentration measurement include physical particle diameter less than 10 µm (PM 10), formaldehyde and carbon dioxide (CO 2 ), carbon monoxide (CO), nitrogen dioxide (NO 2 ), total volatile organic compounds (TVOC), benzene, toluene, ethyl benzene, xylene, styrene, bacteria and fungi of aerosol [6].…”
Section: Introductionmentioning
confidence: 99%